Prototype of M-student application / Safwan Hashan …[et al.] - Hashan, Safwan; Mangsor, Muhammad Amirulzaman; Mohd Shafie, Mohammad Fadzli (2013)
As mobile devices become a trend in modern lifestyle, a new approach is required because mobile devices appeared to be smaller compared to the current devices used to surf the Internet which is the computer. However, most of the mobile user nowadays faced problem and difficulties when they surf the Internet. In some situation they feel awkward due to the nature of the mobile device itself. Besides, mobile device depend fully on wireless connection and the data transfer rate is lower than the computer. This project will convert the I-Student portal of UiTM into a mobile application called Prototype of M-Student Application. The Prototype of MStudent Application will have a small interactive interface that suit nicely with the size of the screen on mobile devices. The flow of the Prototype of M-Student Application is much simpler to provide a smooth surfing experience for the user. In this project, the mobile application is developed using Eclipse editor while the web service is developed using PHP and MySQL. It is hope that from the Prototype of M-Student Application developed it will solve the problem arise and therefore provide a better surfing experience for the mobile user in general and the UiTM student using the I-Student portal in specific.